Solve the equation after making the appropriate substitution. Need help!
![Solve the equation after making the appropriate substitution Need help class=](https://us-static.z-dn.net/files/de6/c22ed3160a66764c490b958270d5648c.png)
Answer:
Step-by-step explanation:
First realize that
[tex](x^{1/3})^{2}=x^{2/3}[/tex]
Usually when you are asked to solve making a substitution you need to find substitute a term leaving a quadratic equation.
if you replace:
[tex]x^{1/3}=u[/tex]
[tex]u^{2}-3u-18 = 0 \\(u-6)(u+3)= 0 \\u = 6 \\u = -3 \\x^{1/3} = 6 => x = 6^{3} = 216\\x^{1/3} = -3 => x = (-3)^{3} = -27[/tex]